2013
DOI: 10.7150/jgen.3741
|View full text |Cite
|
Sign up to set email alerts
|

Topics in Transcriptional Control of Lipid Metabolism: from Transcription Factors to Gene-Promoter Polymorphisms

Abstract: The central dogma of biology (DNA>>RNA>>Protein) has remained as an extremely useful scaffold to guide the study of molecular regulation of cellular metabolism. Molecular regulation of cellular metabolism has been pursued from an individual enzyme to a global assessment of protein function at the genomic (DNA), transcriptomic (RNA) and translation (Protein) levels. Details of a key role by inhibitory small RNAs and post-translational processing of cellular proteins on a whole cell/global basis are now just eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…Expression of Pparg and Cebpa exhibited an agerelated increase in female mice that was most distinct in the old at Day 7 (for both Pparg and Cebpa) and Day 21 (Pparg only). The abundance and maintenance of Pparg expression at both Days 7 and 21 compared to Cebpa suggests a more prominent role in age-and sex-related differences in adipocyte area consistent with previous publications demonstrating that Cebpa acts through induction of Pparg and was not required to promote adipogenesis (32). Thus, sustained elevations of Pparg in old female mice may be a mechanism for the elevated adipocyte area present in old females after CTX injury.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Expression of Pparg and Cebpa exhibited an agerelated increase in female mice that was most distinct in the old at Day 7 (for both Pparg and Cebpa) and Day 21 (Pparg only). The abundance and maintenance of Pparg expression at both Days 7 and 21 compared to Cebpa suggests a more prominent role in age-and sex-related differences in adipocyte area consistent with previous publications demonstrating that Cebpa acts through induction of Pparg and was not required to promote adipogenesis (32). Thus, sustained elevations of Pparg in old female mice may be a mechanism for the elevated adipocyte area present in old females after CTX injury.…”
Section: Discussionsupporting
confidence: 88%
“…promote adipogenesis, Pparg and Cebpa (32) in old age female mice. In addition, young females had increased Ly6C + pro-inflammatory monocytes/macrophages preceding the increased Sca-1 + CD45 − cells compared to young male mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Transcriptome- and genome-wide association analyses and epigenetic studies are widely used to reveal the molecular pathological mechanisms of MAFLD. A large number of valuable genes of lipid metabolism have been shown to regulate by several important transcription factors, such as PPARs , FXR , C/EBPs , SREBPs and Zfp423 ( 37 ). The transcription factors associated with the MAFLD, including FXR agonists and PPAR-α/δ agonists, have been studied in late-stage clinical trials to treat NASH ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…situations (Bergen & Burnett, 2012). Moreover, recent studies have shown the ability of the mature adipocyte to dedifferentiate returning into a proliferative state Fernyhough, Hausman, & Dodson, 2008;Kokta, Dodson, Gertler, & Hill, 2004) resulting in different cell lineages such as myogenesis (Dodson et al, 2010;Kazama, Fujie, Endo, & Kano, 2008;Matsumoto et al, 2008;Wei et al, 2012).…”
Section: Tablementioning
confidence: 99%